The overdose epidemic: a study protocol to determine whether people who use drugs can influence or shape public opinion via mass media - Ehsan Jozaghi; VANDU (BMC, 2022)
Abstract Background We are currently witnessing an ongoing drug overdose death epidemic in many nations linked to the distribution of illegally manufactured potent synthetic opioids. While many health policy makers and researchers have focused on the root causes and possible solutions to the current crisis, there has been little focus on the power of advocacy and community action by people who use drugs (PWUDs). Specifically, there has been no research on the role of PWUDs in engaging and influencing mass media opinion. Methods By relying on one of the longest and largest peer-run drug user advocacy groups in the world, the Vancouver Area Network of Drug Users (VANDU), newspaper articles, television reports, and magazines that VANDU or its members have been directly involved in will be identified via two data bases (the Canadian Newsstream & Google News). The news articles and videos related to the health of PWUDs and issues affecting PWUDs from 1997 to the end of 2020 will be analyzed qualitatively using Nvivo software. Discussion As our communities are entering another phase of the drug overdose epidemic, acknowledging and partnering with PWUDs could play an integral part in advancing the goals of harm reduction, treatment, and human rights.